The Effect of Current Ratio and Total Asset Turn Over on Return on Assets at Bank Sumut KC. Syariah Pematang Siantar Periode 2017-2021 - Vera, Rahmi; Nurlaila, Nurlaila; Kusmilawaty, Kusmilawaty (STIE Indonesia Banking School, 2023)
This research aims to determine whether there is an influence of Current Ratio and Total Asset Turn Over on Return on Assets at Bank Sumut KC. Syariah Pematang Siantar using a quantitative approach. The data used in the research is secondary data obtained from published reports in a monthly time series from 2017 to 2021. The data was analyzed using multiple linear regression. The results of the research show that (1) the Current Ratio variable has a negative and insignificant influence on Return on Assets at Bank Sumut KC. Pematang Siantar Sharia. (2) The Total Asset Turn Over variable has a positive and significant influence on Return on Assets at Bank Sumut Branch Pematang Siantar Sharia. (3) The variables Current Ratio and Total Asset Turn Over simultaneously influence Return on Assets at Bank Sumut KC. Pematang Siantar Sharia.